Experimental model of multidetector device based on CdZnTe detectors - Batiy, V.G.; Nenakhov, A.N.; Pravdiviy, A.A.; Kochnev, N.A.; Selyukova, V.V.; Khazhmuradov, M.A. (Вопросы атомной науки и техники, 2005)
The multidetector device for measurement of angular distributions of intensity of gamma - radiation is described.
Results of tests of experimental model of device are presented and prospects of use of such device are shown. Описано багатодетекторну установку для вимірювання кутових розподілів інтенсивності гамма-
випромінювання. Приведено результати випробувань дослідної моделі установки і показано перспективи
використання такої установки. Описана многодетекторная установка для измерения угловых распределений интенсивности гамма-
излучения. Приведены результаты испытаний опытной модели установки и показаны перспективы
использования такой установки.